Working Together towards the Sub-mSv CT Exam - Denison, K (Nepalese Journal of Radiology, 2013)
Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 51-54 DOI: http://dx.doi.org/10.3126/njr.v2i2.7685